Statistical Abstract of the Arab Region, Issue No. 33 - United Nations (United Nations, 2013)
The thirty-third issue of the Statistical Abstract of the Arab Region presents time series statistics and indicators on economic and social issues in all fourteen Arab Region member countries. The Abstract is divided into twelve chapters addressing the following topics: population; labour force; education and illiteracy; health; gender equality; national accounts; energy; industry; transport; foreign trade; financial statistics and prices; and information and communications technology. Data contained in the Abstract were primarily collected from national statistical sources in the Arab Region, either through responses to questionnaires or from statistical abstracts and bulletins issued by official authorities in member countries. The Abstract also relies on data issued by international organizations and agencies, with priority given to United Nations sources.